Otic Neurogenesis Is Regulated by TGFβ in a Senescence-Independent Manner - Magariños, Marta; Barajas-Azpeleta, Raquel; Varela-Nieto, Isabel; R. Aburto, Maria (Frontiers in Cellular Neuroscience, 2020)
Cellular senescence has classically been associated with aging. Intriguingly, recent studies have also unravelled key roles for senescence in embryonic development, regeneration, and reprogramming. Developmental senescence has been reported during embryonic development in different organisms and structures, such as the endolymphatic duct during inner ear development of mammals and birds. However, there is no study addressing the possible role of senescence on otic neurogenesis. TGFβ/SMAD is the best-known pathway linked to induction of developmental programmed cell senescence. Here, we studied if TGFβ2 induces cellular senescence during acoustic-vestibular-ganglion (AVG) formation. Using organotypic cultures of AVG, and characterizing different stages of otic neurogenesis in the presence of TGFβ2 and a selective TGF-β receptor type-I inhibitor, we show that TGFβ2 exerts a powerful action in inner ear neurogenesis but, contrary to what we recently observed during endolymphatic duct development, these actions are independent of cellular senescence. We show that TGFβ2 reduces proliferation, and induces differentiation and neuritogenesis of neuroblasts, without altering cell death. Our studies highlight the roles of TGFβ2 and cellular senescence in the precise regulation of cell fate within the developing inner ear and its different cell types, being their mechanisms of action highly cell-type dependent.